Removal of endobronchial mucormycosis lesion through a rigid bronchoscope. Issue 3 (March 1992) - al-Majed, S; al-Kassimi, F; Ashour, M; Mekki, M O; Sadiq, S
Abstract : A 44 year old man with poorly controlled diabetes mellitus developed endobronchial mucormycosis, which totally obstructed the right lower lobe bronchus. The lesion was removed through a rigid bronchoscope. Two weeks later the bronchus was free of mucormycosis histologically and on culture.